2017
DOI: 10.1080/0886022x.2017.1279553
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of a dipeptidyl peptidase 4 inhibitor in a mouse model of progressive renal fibrosis

Abstract: Although the effects of dipeptidyl peptidase 4 (DPP-4) inhibitors beyond their hypoglycemic action have been reported, whether these inhibitors have renoprotective effects in nondiabetic chronic kidney disease (CKD) is unclear. We examined the therapeutic effects of DPP-4 inhibition in mice with unilateral ureteral obstruction (UUO), a nondiabetic model of progressive renal fibrosis. After UUO surgery, mice were administered either the DPP-4 inhibitor alogliptin or a vehicle by oral gavage once a day for 10 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…These findings support the therapeutic potential of GLP‐1 and adenosine interactions for myocardial infarction and heart failure . In mouse model of renal fibrosis, the expression of PAI‐1 and TGF‐β, as well as interstitial infiltration of macrophages tended to be reduced and tubulointerstitial fibrosis suppressed by alogliptin administered orally 40 mg/kg once daily for 10 days . This gliptin at oral dose of 20 mg/kg daily for 1 week little decreased levels of IL‐1β, ‐6 and reduced macrophages infiltration via GLP‐1‐dependent signaling in the kidney in rat nondiabetic model of glomerular injury …”
Section: Suppression Of Inflammatory Mediators and Pathways In Vasculsupporting
confidence: 66%
See 1 more Smart Citation
“…These findings support the therapeutic potential of GLP‐1 and adenosine interactions for myocardial infarction and heart failure . In mouse model of renal fibrosis, the expression of PAI‐1 and TGF‐β, as well as interstitial infiltration of macrophages tended to be reduced and tubulointerstitial fibrosis suppressed by alogliptin administered orally 40 mg/kg once daily for 10 days . This gliptin at oral dose of 20 mg/kg daily for 1 week little decreased levels of IL‐1β, ‐6 and reduced macrophages infiltration via GLP‐1‐dependent signaling in the kidney in rat nondiabetic model of glomerular injury …”
Section: Suppression Of Inflammatory Mediators and Pathways In Vasculsupporting
confidence: 66%
“…GLP‐1‐mediated cardioprotection by alogliptin was shown in dogs . This gliptin exerted renoprotective effects in terms of attenuation of inflammation and fibrosis in mice and rats …”
Section: Suppression Of Inflammatory Mediators and Pathways In Vasculmentioning
confidence: 98%
“…Since FBs also constitute the center of fibrotic disease etiology in other organs, this finding might have important implications beyond the skin. 1,60 In animal studies, DPP4 + FBs have been shown to be involved in fibrotic pathologies of several other organs, and inhibition of DPP4 activity by gliptins attenuated fibrotic processes in the lung, 61 heart, 62,63 kidney, 64 and liver. 65 Therefore, our transcriptome analysis of DPP4 + FBs in the human skin might represent an important step toward the development of novel anti-fibrotic therapeutic approaches, specifically targeting the DPP4 + FB subset.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, DPP-4 inhibitors have been reported to attenuate cisplatin-induced AKI in mice and rats via inhibition of tubular cell death [4,5]. It has also been reported that DPP-4 inhibitors can prevent AKI induced by ischemia-reperfusion and chronic kidney injury in several animal models [6][7][8][9][10]. However, it remains to be investigated whether DPP-4 inhibitors can attenuate kidney injury in human patients.…”
Section: Introductionmentioning
confidence: 99%